Phenylpyrroles: 30 Years, Two Molecules and (Nearly) No Resistance - Kilani, Jaafar; Fillinger, Sabine (Frontiers in Microbiology, 2016)
Phenypyrroles are chemical analogs of the natural antifungal compound pyrrolnitrine. Fenpiclonil, but mainly fludioxonil are registered against multiple fungal crop diseases since over 25 years for seed or foliar treatment. They have severe physiological impacts on the pathogen, including membrane hyperpolarization, changes in carbon metabolism and the accumulation of metabolites leading to hyphal swelling and burst. The selection and characterization of mutants resistant to phenylpyrroles have revealed that these fungicides activate the fungal osmotic signal transduction pathway through their perception by a typical fungal hybrid histidine kinase (HHK). The HHK is prone to point mutations that confer fungicide resistance and affect its sensor domain, composed of tandem repeats of HAMP motifs. Fludioxonil resistant mutants have been selected in many fungal species under laboratory conditions. Generally they present severe impacts on fitness parameters. Since only few cases of field resistance specific to phenylpyrroles have been reported one may suspect that the fitness penalty of phenylpyrrole resistance is the reason for the lack of field resistance.